Evaluating economic and ecological management to determine the economic size of pastoral units for different climatic zones in the northeast of Iran - Haghiyan, Iman; Mofidi-Chelan, Morteza; Azadi, Hossein; Nejatiyanpour, Elnaz; Motamedi, Javad; Sheidai-Karkaj, Esmaeil; Scheffran, Jürgen (Journal of environmental management, 2022)
Stocking rate and rangeland area are key variables to provide the livelihood of herders in different climatic zones. To evaluate the economic and ecological management of pastoral units, this study aims to determine the optimal economic size of pastoral units for livestock grazing use considering the ecological capacity of semi-arid rangelands in different climatic scenarios. Therefore, 12 pastoral units (an area of 47,355 ha) were selected in two climatic zones (summer and winter rangelands) in the Kalat region of Razavi Khorasan Province, Iran. By measuring forage production, carrying capacity was calculated. Based on the results, the costs of traditional livestock management in winter rangelands are higher than those of summer rangelands. Moreover, the current size of the assigned rangeland, especially the summer rangeland, is lower than that of the economic justification. The results emphasize that rangeland-based livestock husbandry cannot create a good livelihood for herders in the region, and it is necessary to pay special attention to other services and aspects, despite the existing ecological and socio-economic complexities. In this regard, providing multi-purpose rangeland use and useable technologies to better manage these areas is necessary to increase per capita household income and reduce the stocking rate in the region's rangelands. Ultimately, both increasing the level of available rangelands and reducing costs by applying new technology are required, as is the economic consideration of pastoral units by using rangelands for multiple purposes.
Keywords: zachování přírodních zdrojů; Animals; Livestock; Herders' livelihood; Seasons; Írán; zvířata; Iran; Traditional livestock management; Conservation of Natural Resources; Forage production; roční období; dobytek; Summer and winter rangelands